The Gβ1 and Gβ3 Subunits Differentially Regulate Rat Vascular Kv7 Channels - Greenwood, Iain A.; Stott, Jennifer B. (Frontiers in Physiology, 2020)
Within the vasculature Kv7 channels are key regulators of basal tone and contribute to a variety of receptor mediated vasorelaxants. The Kv7.4 isoform, abundant within the vasculature, is key to these processes and was recently shown to have an obligatory requirement of G-protein βγ subunits for its voltage dependent activity. There is an increasing appreciation that with 5 Gβ subunits and 12 Gγ subunits described in mammalian cells that different Gβxγx combinations can confer selectivity in Gβγ effector stimulation. Therefore, we aimed to characterise the Gβ subunit(s) which basally regulate Kv7.4 channels and native vascular Kv7 channels. In Chinese Hamster Ovary cells overexpressing Kv7.4 and different Gβx subunits only Gβ1, Gβ3 and Gβ5 enhanced Kv7.4 currents, increasing the activation kinetics and negatively shifting the voltage dependence of activation. In isolated rat renal artery myocytes, proximity ligation assay detected an interaction of Kv7.4 with Gβ1 and Gβ3 subunits, but not other isoforms. Morpholino directed knockdown of Gβ1 in rat renal arteries did not alter Kv7 dependent currents but reduced Kv7.4 protein expression. Knockdown of Gβ3 in rat renal arteries resulted in decreased basal K+ currents which were not sensitive to pharmacological inhibition of Kv7 channels. These studies implicate the Gβ1 subunit in the synthesis or stability of Kv7.4 proteins, whilst revealing that the Gβ3 isoform is responsible for the basal activity of Kv7 channels in native rat renal myocytes. These findings demonstrate that different Gβ subunits have important individual roles in ion channel regulation.